Identifying the predictors of avoidable emergency department attendance after contact with the NHS 111 phone service: analysis of 16.6 million calls to 111 in England in 2015–2017. Issue 3 (9th March 2020) - Egan, Mark; Murar, Filip; Lawrence, James; Burd, Hannah
Abstract : Objectives: To measure the frequency of patients making avoidable emergency department (ED) attendances after contact with NHS 111 and to examine whether these attendances can be predicted reliably. Design: Analysis of 16 563 946 calls made to 111, where each call was linked with a record of whether the patient attended ED within 24 hours. Setting: All regions of England from March 2015 to October 2017. Participants and data: Our main regression model used a sample of 10 954 783 calls, each with detailed patient-level information. Main outcome: Whether patients made an unadvised, non-urgent type 1 ED ('avoidable') attendance within 24 hours of calling 111. Results: Of 16 563 946 calls to 111, 12 894 561 (77.8%) were not advised to go to ED (ie, they were advised to either attend primary care, attend another non-ED healthcare service or to self-care). Of the calls where the patient was not advised to go to the ED, 691 783 (5.4%) resulted in the patient making an avoidable ED attendance within 24 hours. Among other factors, calls were less likely to result in these attendances when they received clinical input (adjusted OR 0.52, 95% CI 0.51 to 0.53) but were more likely when the patient was female (OR 1.07, 95% CI 1.06 to 1.08) or aged 0–4 years (OR 1.34, 95% CI 1.33 to 1.35). Conclusions: For every 20 calls where 111 did not advise people to attend the ED, 1 resulted in avoidable ED attendance within 24 hours. These avoidable attendances could be predicted, to a certain extent, based on call characteristics. It may be possible to use this information to help 111 call handlers identify which callers are at higher risk of these attendances.